(untitled) (KYAMC Journal, 2017)
Background: Acute coronary syndrome (ACS) is a common cause of disability and death, and when it happens in young individuals, it causes more social and economic disadvantages. Gender differences have been identified in nearly every aspect of cardiovascular disease including acute coronary syndrome. Several studies reported differences between men and women in the clinical presentation & risk factors of acute coronary syndromes. Methods: In this observational analytic study a total 115 patients (75 males and 40 females) under 45 years presenting with acute coronary syndrome were enrolled to see the gender differences in clinical presentation and risk factors. Results: The mean age in males was 36.6±4.8 years and in female 39.0±3.8 years. Chest pain was the main presenting complaints in both sexes but atypical presentation was significantly higher in females. Smoking was the most common risk factor in males and hypertension & diabetes were significantly higher in females. Females mostly diagnosed as Unstable Angina and NSTEMI and males as STEMI. Conclusion: There are significant differences between males and females in respect to clinical presentation and risk factors in acute coronary syndrome under 45 years of age. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 620-622